2021
DOI: 10.1002/agj2.20655
|View full text |Cite
|
Sign up to set email alerts
|

Interseeded pennycress and camelina yield and influence on row crops

Abstract: Field pennycress (Thlaspi arvense L.) (PC) and winter camelina [Camelina sativa (L.) Crantz] (WC) have the potential to provide ecosystem services and economic incentives when adopted as an oilseed cover crops in corn (Zea mays L.)-soybean [Glycine max (L.) Merr.] rotations. However, PC and WC establishment and yield in the northern Corn Belt and their subsequent impact on row crops are not well known.This study was conducted to determine the effects of interseeding dates (R4, R5, and R6; and R6, R7, and R8 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
0
20
2
Order By: Relevance
“…Berti et al (2015) reported 47% and 71% soybean seed yield reduction in Morris and Prosper, respectively, in relay cropping with camelina compared with sole soybean planted at the normal seeding date. However, in contrast to some studies reporting soybean yield losses offset by camelina seed yield (Gesch et al 2014;Johnson et al 2017Johnson et al , 2015Ott et al 2019), in our study soybean seed yield losses were not offset by the winter crops seed yield (Patel et al 2021), causing a lower net margin. A very limited or even negligible impact of the cover crop on the main crop yield is often reported in literature, mainly because the cover crop is interseeded after the weed free critical period of the main cash crop has passed (Snapp et al 2005).…”
Section: Environmental Trade-offs and Economic Sustainabilitycontrasting
confidence: 99%
“…Berti et al (2015) reported 47% and 71% soybean seed yield reduction in Morris and Prosper, respectively, in relay cropping with camelina compared with sole soybean planted at the normal seeding date. However, in contrast to some studies reporting soybean yield losses offset by camelina seed yield (Gesch et al 2014;Johnson et al 2017Johnson et al , 2015Ott et al 2019), in our study soybean seed yield losses were not offset by the winter crops seed yield (Patel et al 2021), causing a lower net margin. A very limited or even negligible impact of the cover crop on the main crop yield is often reported in literature, mainly because the cover crop is interseeded after the weed free critical period of the main cash crop has passed (Snapp et al 2005).…”
Section: Environmental Trade-offs and Economic Sustainabilitycontrasting
confidence: 99%
“…Additionally, camelina oil in the present study (385 g kg −1 average) was much greater than that in the Patel et al. (2021) study which averaged 315 g kg −1 when following corn. These authors attributed low camelina productivity under such interseeded systems to stress and growth suppression caused by a combination of lack of light during seedling development under the corn canopy followed by residue that covered the plants following grain harvest.…”
Section: Discussioncontrasting
confidence: 72%
“…This yield is approximately four-times greater than the overall yield reported for winter camelina interseeded into standing corn across three different seeding dates (R4, 5, and 6 stages of corn) over four locations spanning south and western Minnesota, eastern North Dakota, and central Iowa (Patel et al, 2021). Additionally, camelina oil in the present study (385 g kg −1 average) was much greater than that in the Patel et al (2021) study which averaged 315 g kg −1 when following corn. These authors attributed low camelina productivity under such interseeded systems to stress and growth suppression caused by a combination of lack of light during seedling development under the corn canopy followed by residue that covered the plants following grain harvest.…”
Section: Crop Sciencementioning
confidence: 73%
See 2 more Smart Citations